Ways to Increase Efficiency in Teaching the Topic of “Ball Bearing” - Rakhimov Rakhimjon Rajapboevich (Zien Journals, 2022)
This article discusses how to design a "ball bearing" in the Siemens NX program. These include: Drawing the outer and inner bearing of a ball bearing, drawing a ball bearing ball, and assembling a ball bearing in Siemens NX.
Keywords: Designing; a technique; a ball; ball bearing